A Model for Phylogenetic Chemosystematics: Evolutionary History of Quinones in the Scent Gland Secretions of Harvestmen - Raspotnig, Günther; Schaider, Miriam; Föttinger, Petra; Schönhofer, Axel (Frontiers in Ecology and Evolution, 2017)
By the possession of unique exocrine scent glands, Opiliones (harvestmen) arise as a perfect model for studies on the evolutionary history of secretion chemistry. Among gland compounds of harvestmen, it is the quinones that represent recurring elements across the secretions of all suborders. Reliable data on quinone-distribution, however, is only known for Laniatores (benzoquinones) and Cyphophthalmi (naphthoquinones). We here unraveled the quinone-distribution across scent gland secretions of the third large harvestman suborder, the Palpatores (= Eu- and Dyspnoi): Naphthoquinones were found in phalangiid Eupnoi across all subfamilies as well as in nemastomatid (and at least one ischyropsalid) Dyspnoi. Benzoquinones (1,4-benzoquinone) were restricted to a small entity within Eupnoi, namely platybunine Phalangiidae, probably misplaced Gyantinae (currently Sclerosomatidae) and Amilenus (incertae sedis). Our findings, combined with data from Laniatores and Cyphophthalmi, allow evaluation of a comprehensive chemosystematic model for Opiliones for the first time. Evolutionary scenarios imply naphthoquinones as scent gland compounds of common ancestry, having evolved in an early harvestman ancestor and present in cyphophthalmids and palpatoreans, but lost in laniatoreans. Benzoquinones evolved later and independently at least twice: once in the secretions of gonyleptoid Laniatores (alkylated benzoquinones), and a second time in a lineage of phalangiid Eupnoi (1,4-benzoquinone).